PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR KECAMATAN SAMARINDA ULU - Welly; Sri Hayati Ginting; Maria Lidia Davega (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2025)
The analytical tools used are multiple linear regression, partial correlation, multiple correlation, determination, partial test (t test) and simultaneous test (f test) which previously carried out instrument tests (validity test and reliability test) and classical assumption tests (normality test, multicollinearity test, heteroscedasticity test) with a population of 45 people by determining the sample size using a saturated sample. From the multiple linear regression analysis, the equation Y = 22.823 - 0.372X1 + 0.212X2 is obtained. This means that an increase in one level of employee performance is caused by the work environment by -0372 units and is caused by work motivation by 0.212 units. If the work environment and work motivation are ignored, employee performance will only be a constant value of 22.823. From the multiple correlation analysis, the value of R = 0.321 is obtained, meaning that there is a low relationship between the work environment and work motivation and employee performance. Partially, the correlation between the work environment and employee performance is (rx1y = 0.120), the correlation between work motivation and employee performance is (rx2y = 0.172). The coefficient of determination R2 (R Square) is 0.321 or 32.1%, meaning that the work environment and work motivation simultaneously contribute 32.1% to employee performance and the remaining 67.9% is contributed by many other variables outside the work environment and work motivation. which is being researched.